A Search for Two Types of Transverse Excitations in Liquid Polyvalent Metals at Ambient Pressure: An Ab Initio Molecular Dynamics Study of Collective Excitations in Liquid Al, Tl, and Ni - Bryk, Taras; Demchuk, Taras; Jakse, Noël; Wax, Jean-François (Frontiers in Physics, 2018)
Recent findings of pressure-induced emergence of unusual high-frequency contribution to transverse current spectral functions in several simple liquid metals at high pressures raised a question whether similar features can be observed in liquid metals at ambient conditions. We report here analysis of ab initio molecular dynamics-derived longitudinal (L) and transverse (T) current spectral functions and corresponding dispersions of collective excitations in liquid polyvalent metals Al, Tl, Ni. We have not found evidences of the second branch of high-frequency transverse modes in liquid Al and Ni, while in the case of liquid Tl they were clearly present in transverse dynamics. The vibrational density of states for liquid Tl has a pronounced high-frequency shoulder, which is located right in the frequency range of the second high-frequency transverse branch, while for liquid Al and Ni the vibrational density of states has only a weak indication of possible high-frequency shoulder. The origin of specific behavior of transverse excitations in liquid Tl is discussed.